A Stylistic approach to Theodore Roethke's poetry - Jañon, Ma. Asuncion C. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1989)
This thesis constitutes a brief biographical sketch of Theodore Roethke, a stylistic analysis of ten of his poems: Dolor, Open House, Root Cellar, Weed Puller, The Meadow Mouse, Cutting and Cuttings (later), The Bug, In the Time of Change and Early Flower. The seven poems in succession are found in his anthology pf poems, The Collected poems of Theodore Roethke (1966), while the last three are from his previously uncollected poems. Also, the thesis includes an evaluation and discussion of the poems in the light of the poet's biography. The linguistic method used for the evaluation and discussion of the poems in the light of the poet's biography. The linguistic method used for the evaluation of the poems is a stylistic approach, an analysis of the lexicon which involves lexical cohesion, Foregrounding and Cohesion of Foregrounding. Furthermore, the stylistic analysis of the lexicon provides for the identification of Roethke's main themes: the theme of loss and the theme of struggle , as exemplified by his poems. The thesis concludes by saying that Roethke's poems are nostalgic, full of memories and reverence for the past. Also, the thesis supports the idea that Roethke's poems constitute a kind of spiritual autobiography. The poem speaks of Roethke himself. A compilation of works by Roethke and criticisms or critical studies about his works are found after the text. There is also a list of books that can be used for an introduction to stylistics, this comrises only a general theory about the stylistic method. For a particular method of analysis such as, an analysis of the poems' meter and stress, a book edited by Donald G. Freeman, Essays in Modern Stylistics. London and New York: Methuen, 1981, can provide a good start for a research in the field. There is also an anthology of the poems used in the thesis and also, poems that were mentioned, quite in passing, the purpose of which is to provide available information.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.